Psychosociální problematika prostituce - Benešová, Marie (2006)
Presented master' s thesis "Psychosocial problems of the prostitution" inquires into specific aspects of this socialy pathological phenomenon. Whole study includes theoretical and practical part. Opening chapters of the theoretical part present the definition of prostitution and the summary of its specifics, moreover they concern the theory of causes of prostitution and its transformation during the history. Following chapters present different forms of prostitution, including the characteristic of some of them, and above all they talk about the psychological and social aspects of causes, which bring a woman to practise the prostitution, about the selfperception of women-prostitute and about her relationship with her partner or family. The work covers also some negative social factors of prostitution such as the spread of venereal deseases or the connection with the organised crime. In addition in includes the possibilities of the government to solve the problem of prostitution and it summarizes the evolution of juridical situation in Czech Republic during the 20th century. Because of actual conditions, which occurred during the work with this clientele, there was not chance of question-form exploration or psychological test. The practical part documents the possibilities of the resocialisation and aid to...